229k views
3 votes
Which expression is equivalent to (2g^3+4)^2

2 Answers

2 votes

Answer:

+64g^6 + 64g^3 + 16. I think

Step-by-step explanation:


{( {2g}^(3) +4)}^(2) = {(8 {g}^(3) + 4) }^(2) =


(8 {g}^(3) + 4) *(8 {g}^(3) + 4) = 64 {g}^(6) + 32 {g}^(3) + 32 {g}^(3) + 16 = 64 {g}^(6) + 64 {g}^(3) + 16

User Xruptronics
by
5.3k points
4 votes

Answer with explanation:

Two expression are said to be equivalent, if we replace the variable by some constant say 'w' in both the expressions the two expression , that is original expression and Equivalent expression yields the same numerical value.

The given expression is:


(2 g^3 +4)^2=(2 g^3)^2+4^2+2 * (2 g^3) * 4\\\\=4 g^6+16 +16 g^3

is an equivalent expression of the expression given.

Used the identity

⇒(a +b)²=a²+b²+2 a b

User Xharze
by
3.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.